It Takes Two to Tango: How a Dysregulation of the Innate Immunity, Coupled With Candida Virulence, Triggers VVC Onset - Ardizzoni, Andrea; Wheeler, Robert T.; Pericolini, Eva (Frontiers in Microbiology, 2021)
Vulvovaginal candidiasis (VVC) is a symptomatic inflammation of the vagina mainly caused by C. albicans. Other species, such as C. parapsilosis, C. glabrata, C. tropicalis and C. krusei, are mainly associated to the recurrent form of the disease (RVVC), although with a lower frequency. In its yeast form, C. albicans is tolerated by the vaginal epithelium, but switching to the invasive hyphal form, co-regulated with the expression of genes encoding virulence factors such as Sap and candidalysin, allows for tissue damage. Vaginal epithelial cells play an important role by impairing C. albicans tissue invasion through several mechanisms such as epithelial shedding, secretion of mucin and strong interepithelial cell connections. However, morphotype switching coupled to increasing of the fungal burden can overcome the tolerance threshold and trigger an intense inflammatory response. Pathological inflammation is believed to be facilitated by an altered vaginal microbiome, i.e., Lactobacillus dysbiosis. Notwithstanding the damage caused by the fungus itself, the host response to the fungus plays an important role in the onset of VVC, exacerbating fungal-mediated damage. This response can be triggered by host PRR-fungal PAMP interaction and other more complex mechanisms (i.e., Sap-mediated NLRP3 activation and candidalysin), ultimately leading to strong neutrophil recruitment. However, recruited neutrophils appear to be ineffective at reducing fungal burden and invasion; therefore, they seem to contribute more to the symptoms associated with vaginitis than to protection against the disease. Recently, two aspects of the vulvovaginal environment have been found to associate with VVC and induce neutrophil anergy in vitro: perinuclear anti-neutrophil cytoplasmic antibodies (pANCA) and heparan sulfate. Interestingly, CAGTA antibodies have also been found with higher frequency in VVC as compared to asymptomatic colonized women. This review highlights and discusses recent advances on understanding the VVC pathogenesis mechanisms as well as the role of host defenses during the disease.